2016
DOI: 10.1016/j.jvs.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Complementary roles of open and hybrid approaches to thoracoabdominal aortic aneurysm repair

Abstract: Objective Thoracoabdominal aortic aneurysm (TAAA) repair remains a significant challenge with considerable perioperative morbidity and mortality. A hybrid approach visceral debranching with endovascular aneurysm exclusion has been used to treat high-risk patients and therefore to allow repair in more patients. Limited data exist regarding long-term outcomes with this procedure as well as comparison to conventional open repair. This study describes our institutional algorithmic approach to TAAA repair using bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 44 publications
2
40
1
1
Order By: Relevance
“…A limitation of hybrid TAAA repair involves endoleaks probably secondary to aortic remodeling over time and long-segment endografts implanted for aneurysm exclusion [40]. In scientific literature, the incidence of endoleaks is variable in different series (Table 21.1) but is a matter of concern because it may expose patients to future reintervention and may leave them at risk of aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of hybrid TAAA repair involves endoleaks probably secondary to aortic remodeling over time and long-segment endografts implanted for aneurysm exclusion [40]. In scientific literature, the incidence of endoleaks is variable in different series (Table 21.1) but is a matter of concern because it may expose patients to future reintervention and may leave them at risk of aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report comparing 84 conventional open and 81 hybrid repairs, despite the greater comorbidity burden in the hybrid group, with a significantly higher rate of preoperative chronic renal failure (a well-known independent predictor of mortality), there were no differences in the in-hospital mortality or spinal cord ischemia rates, while patients in the conventional group presented more strokes (9.5% vs. 0%, P=0.017) and those in the hybrid group a significantly increased rate of definitive dialysis (14.8% vs. 3.6%, P=0.043) and higher reintervention rates (12.3% vs. 1.2%, P=0.004), mainly due to endoleaks. Both groups had equivalent survival rates at the first year (hybrid 69% vs. open 77%) and similar longterm aorta-specific survival, suggesting that both techniques can have complementary roles and that the coexistence of several options for treatment of TAAAs in a single centre allows for the treatment of a greater number of patients (65).…”
Section: Endoleaksmentioning
confidence: 94%
“…Conventional surgery is still associated with substantial perioperative morbi-mortality rates, especially in the elderly and fragile patients, which are however, the fastest growing segment of the population. A recent report comparing open and hybrid repair for TAAA showed that patients selected for hybrid procedures were significantly older and showed greater comorbidities (12). Despite this fact, there were no significant differences in the in-hospital mortality and postoperative paraplegia rates between the two groups.…”
Section: Case Presentationmentioning
confidence: 97%
“…One and five-year survival rates were 69% and 32% respectively, in the hybrid group vs. 77% and 56% in open group. The worse late survival rate appears to be mainly influenced by a higher comorbid disease burden in the hybrid patient group (12). Some authors consider hybrid TAAA repair a procedure with unacceptable morbidity and mortality, suggesting that high-risk patients with TAAA should receive a non-interventional approach (13).…”
Section: Case Presentationmentioning
confidence: 99%